A Quantitative Analysis of in vitro Antioxidant Capacity and Antioxidant Enzymes in Bacopa monnieri (L.) Wettst - Shanmugam, Ramya; Kathirvel, Bharathi; Abidharini, Jothi Dheivasikamani; Gowtham, Pemula; Agnishwar, Girigoswami; Pallavi, Pragya; Prabhu, Jeyabal Philomenathan Antony; Arumugam, Vijaya Anand (Free Radicals and Antioxidants)
Background: Bacopa monnieri (L.) Wettst is an herbal plant used predominantly in Ayurvedic medicine. Though this plant has diverse pharmacological properties it is pivotal to acknowledge its total antioxidant capacity and enzymatic quantification which are not well established. Therefore, the principal objective of this study is to elucidate the antioxidant capacity in five different solvent extracts including ethanol, acetone, chloroform, petroleum ether and aqueous, further to quantify chlorophyll and iron content and the antioxidant enzymes of B. monnieri fresh stem extracts. Materials and Methods: The comparative identification of the antioxidant capacities of five different extracts ethanol, acetone, chloroform, petroleum ether and aqueous of B. monnieri stem was investigated through phosphomolybdate assay (Total antioxidant capacity). The fresh stem extracts were quantified for chlorophyll and iron content using the acetone method and the thiocyanate method respectively, furthermore quantified antioxidant enzymes are Superoxide Dismutase (SOD), Catalase (CAT), Peroxidase (Px), Ascorbate Oxidase (AO) and Polyphenol Oxidase (PPO). Results: The results showed the fresh stem extract has a total chlorophyll content of 0.2720±0.01 mg/g and the iron content is greatly obtained in distilled water than in 30% sulphuric acid. The ethanol extract exhibited greater antioxidant capacity with the IC50 value of 16±0.3 μg/mL. The enzymatic capacity of SOD, CAT, Px, AO and PPO resulted in 10.83±0.003 units of fresh weight, 41.03±0.004, 2.044±0.003, 56.15±0.003 and 57.21±0.003-unit mg-1 protein min-1 respectively. Conclusion: The results indicate that B. monnieri may serve a strong prophylactic action against ROS-related diseases with its remarkable enzymatic defense system and antioxidant capacity.
Keywords: Bacopa monnieri; Chlorophyll; Enzymatic antioxidants; Iron; Phosphomolybdate; Plant extract